The Role of Transformational Leadership in Airline Business Success: A Comparison of Rising Above the Clouds and From Worst to First Book - Deniz Taşcı; Ahmet Ertek (Selçuk Üniversitesi Sosyal Bilimler Meslek Yüksekokulu Dergisi)
The aviation sector is highly affected by technological, political and economic developments. It is an undeniable fact that businesses must keep up with these rapid changes and developments, especially as they are affected by technological developments. The leadership styles and leadership characteristics of the managers are not only effective in the formation of a certain culture, but also in the life course of the enterprises and the processes of adapting to the changes. This adaptation process can be reduced and the faster adaptation can be achieved, the business success will follow in parallel. Based on this view, in our study, the effect of leadership characteristics of managers in airline companies on business success has been examined. The aim of the study is to explain the transformational leadership characteristics of managers in airline companies and the roles of these characteristics in the positive or negative processes of airline businesses. In the study, "Bulutların Üstüne Tırmanırken" and "From Worst To First" books' content analysis was made by considering the subjects of airline management, leadership and transformational leadership. At the end of research; It has been concluded that leaders do not take risks and display an innovative approach in times of crisis.